PEMIKIRAN KEWIRAUSAHAAN KELUARGA MANGKUNEGARAN (History Department, Semarang State University and Historian Society of Indonesia, 2016)
According to the historical event of the Mangkunegaran dinasty said that of entrepreneurship is more striking than the Mataram kingdom such as Kasunanan Surakarta and Kasultanan Yogyakarta Reign. From the time Mangkunegaran I until Mangkunegara IV were successful in plugging the power base of the civil economy proves that the civil Mangkunegaran as one kingdom in Kejawen in the field of entrepreneurship is more advanced than in other Javanese kingdoms. For that reason , this study wanted to find the root network entrepreneurial thinking Mangkunegaran as the focus of the study . This study takes the subject of Mangkunegara thought starting Mangkunegaran I until Mangkunegaran IV. The purpose of this study was to analyze in depth network thought what are strongly held by Sri Mangkunegara I until IV in developing civil entrepreneurial base . The research method used is the historical multidimensional method. The result in this study is that the success of the civil Mangkunegaran in building economic power is highly correlated with entrepreneurial thinking of Mangkunegaran. The thought of Mangkunegara I to IV into civil spirit in building the ethos of entrepreneurship as well as the existence of the family and the kingdom . Although it is epistemological, each kings who ruled differently .Secara historis keberadaan Praja Mang-kunegaran yang unggul dalam bidang kewirausahaan memang lebih maju dari pada kutub-kutub kerajaan Mataram lainnya seperti Kasunanan Surakarta dan Kasultanan Yogyakarta. Penelitian ini ingin mendalami dasar pemikiran kewirausahaan Mangkunegaran. Penelitian ini mengambil fokus pemikiran kewirausahaan Mangkunegaran yang bersumber pada ajaran filosofis Mangkunegara I sampai IV. Tujuan penelitian ini adalah menganalisis secara mendalam pemikiran dan nilai-nilai filosofis yang di pegang teguh oleh Sri Mangkunegara I sampa IV dalam mengembangkan basis kewirausahaan praja. Metode penelitian yang dipakai adalah metode sejarah dengan pendekatan multidimensional. Hasil penelitian menunjukkan bahwa kesuksesan Praja Mangkunegaran dalam membangun kekuatan ekonomi sangat berkorelasi dengan pemikiran filosofis ajaran leluhur Mangkunegaran. Pemikiran filosofis dari Mangkunegara I sampai IV menjadi spirit praja dalam membangun kewirausahaan serta eksistensi trah dan kerajaannya. Walaupun secara epistimologis, masing-masing raja yang memerintah mengaktualisasikannya secara berbeda-beda.